Superalloys 1984 (Fifth International Symposium) 1984
DOI: 10.7449/1984/superalloys_1984_285_294
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Powder Particle Size Distribution and Pressure on the Kinetics of Hot Isostatic Pressing (HIP) Consolidation of P/M Superalloy Rene 95

Abstract: the distribution of particle sizes on the kinetics of densification. The analytical model also suggests HIP conditions for more uniform deformation of all powder particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, these modifications lead to strong segregation in the cast ingots and to a dramatic reduction in formability by forging. According to this, nowadays, a powder metallurgy route called near net shape hot isostatic pressing or (HIPping) is considered very promising to manufacture parts made of those Ni superalloys that are difficult to forge [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17]. This procedure offers a reduction of machining operations and of raw material consumption concerning forging with a consequent reduction of buy to fly ratio as demonstrated by Bassini et al in [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, these modifications lead to strong segregation in the cast ingots and to a dramatic reduction in formability by forging. According to this, nowadays, a powder metallurgy route called near net shape hot isostatic pressing or (HIPping) is considered very promising to manufacture parts made of those Ni superalloys that are difficult to forge [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17]. This procedure offers a reduction of machining operations and of raw material consumption concerning forging with a consequent reduction of buy to fly ratio as demonstrated by Bassini et al in [18].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, they even found that the presence of TiB network structure is beneficial for high temperature strengths [10]. This is contradictory with conventional belief that PPBs decorated by precipitates are harmful for mechanical properties of materials synthesised by powder metallurgy, especially high temperature mechanical properties such as strengths, ductility, creep rupture and fatigue [11][12][13][14][15][16][17][18][19][20][21][22]. It is obvious that for applications, more studies are required to comprehensively investigate the mechanical properties of titanium alloy composites with this kind of network structure.…”
Section: Introductionmentioning
confidence: 90%
“…The HIP process has been modeled by only a few groups [5][6][7][8][9][10][11]. The models assume the powder to be spherical and of either a single size [10,11], or more realistically, a bimodal distribution of sizes [8,9].…”
Section: Hip Modelingmentioning
confidence: 99%
“…For many maturity in the past decade, is now used for the materials, including the high T Q oxide densification of powder consolidates of nuclear superconductors, there are other considerations fuels, tool steels, titanium alloys and other that restrict the preferred sintering temperature, non-ferrous and often refractory alloys, ceramics, For example, for refractory metals and ceramics, composites, and superalloys for critical rotating the melting points are so high that the achievement applications [4][5][6].…”
Section: Introductionmentioning
confidence: 99%